Status of Obesity in Terms of Body Mass Index among Indian Air Force Personnel - L. Robert Varte; D. Majumdar; Shweta Rawat; Inderjeet Singh (Al Ameen Medical College, 2011)
Introduction: This paper investigates the prevalence of obesity (BMI >30 kg/m2) among five geographical groups of Indian Air Force personnel of different age. Purpose of study: To observe the status of obesity among IAF and see whether there is age-wise and regional difference in obesity among the different geographical groups. Results: Gradual increase in mean BMI is seen as age of the population increases. There is an overall marked increase in BMI level among all the three age groups for all the other four zones. F-ratio test of normal range BMI does show significant difference among the zones. There is a statistically significant difference in normal BMI (18.5-24.9 wt/ht2) among all the age groups (F-ratio=11.561, p < 0.05). BMI correlated positively with age in the 20-25 age groups (r = 0.119, p= 0.000) and 26-30 age groups (r = 0.075, p= 0.009) respectively, but BMI did not show any statistically significant correlation with age in the 31-35 age group. Observations: A marked increase in overweight and pre-obese prevalence is seen both age and region wise in the IAF personnel if the Asian BMI cut off levels are applied